A REVIEW OF TAXPAYER SUPERVISION IN EXPLORING SME'S POTENTIAL TAX INCOME TO INCREASE NATIONAL TAX REVENUE IN 2022 ( case study of KPP Pratama Boyolali) - Sasmita, Raymundo Patria Hayu; Atmaja, Elisha Viviana Kusuma; Salim, Meka Sabilla; Karunia, Asaprima Putra (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine the process of activities, contributions, and obstacles as well as efforts that have been taken in supervisory activities in an effort to explore the potential of SME Final Income Tax in 2021 and 2022 at KPP Pratama Boyolali. The results of this study are that there are differences in supervisory activities in an effort to explore the potential of MSME Final PPh at KPP Pratama Boyolali and SE-05/PJ/2022 regarding monitoring of taxpayer compliance, the results of exploring the potential of the business sector contribute greatly to total MSME Final Income Tax receipts but are less contributed to the total revenue at KPP Pratama Boyolali. These monitoring activities are inseparable from obstacles or obstacles, but KPP Pratama Boyolali has made efforts to overcome the obstacles or obstacles that occur.